Influences of motivations and lifestyles on intentions to use smartphone applications. Issue 3 (4th May 2018) - Kim, Juran; Lee, Ki Hoon
Abstract : Mobile advertising, influenced by the current growth in smartphone applications, creates new opportunities for the advertising industry. This study identified motivations for the use of smartphone applications as well as lifestyle clusters of users and examined their influences on the relationships between perceived ease of use, perceived usefulness, attitude and intentions to use. This research used a face-to-face survey and empirical analyses to investigate key questions about how and why consumers use smartphone applications, illustrating the imperative roles that motivations and lifestyle clusters play in an important advertising context. This study represents a step toward clarifying how different lifestyle clusters influence different relationships between motivations, perceived ease of use, perceived usefulness, attitude and intentions to use applications as advertising media, offering implications for advertising academics and practitioners.